Development and validation of a new measurement instrument : the behavioral-cognitive internet security questionnaire (BCISQ) - Velki, Tena (Array, 2019)
Rapid changes in internet use and, consequently, digitalization of almost every aspect of human life lead inevitably to significant problems in information security and social engineering. As previous studies have shown, the biggest problem in internet security is the behavior of internet users. The aim of this study was to develop and validate a new and reliable instrument that would measure information security and awareness of every information-communication user in a short period of time. The development and validation of the new measurement instrument, Behavioral-Cognitive Internet Security Questionnaire (BCISQ), was conducted in three phases. The final version consists of 4 subscales (2 behavioral and 2 cognitive) with a total of 17 items. The results revealed good psychometric characteristics of the BCISQ and showed that a short and reliable questionnaire measuring information security (behavioral aspects of internet security) and users' awareness (cognitive aspects of internet security) was successfully developed.